(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the mean amniotic fluid index with oral versus intravenous maternal hydration for management of females presenting with oligohydramnios in third trimester of pregnancy Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at Idris Teaching hospital Sialkot Medical College Sialkot from Jan 2017 to Jan 2018. Materials and Methods: 200 patients were included in this study, the performa was designed to record the demographic data and lab tests advised and also ultrasound of abdomen of every patients was conducted. The written informed consent was taken from every patient before the start of the study . The permission of Ethical Committee was considered before start of the sampling and publishing in medical forum journal. The Data was analyzed for results on SPSS version 10. Results: In our study the mean age of the patients was 28.68±6.85 years and the mean gestational age of the patients was 32.95±3.18 weeks. The mean value of pre-treatment AFI of the patients was 4.07±0.36cm and the mean value of post-treatment AFI of the patients was 4.09±0.37cm. Statistically there is insignificant difference was found between the post-treatment AFI values with study group i.e. p-value>0.05. Conclusion: It has been proved in our study that there is insignificant difference between oral and intravenous hydration for management of females presenting with oligohydramnios in third trimester of pregnancy.